Banking sector output and labour productivity in six European countries - Leena Mörttinen (Bank of Finland, 2002)
This paper contributes to the discussion on the measurement of banking sector output.It is also a prelude to discussion on possible causes of productivity change in banking.We demonstrate how the banking sector's service production can be measured using aggregate financial statement and payment transactions data.We compute banking sector labour productivity Tornqvist indices for six countries (Finland, Sweden, United Kingdom, Germany, France and Italy) over a period varying from 11 to 20 years.According to the results, Finnish banking sector productivity has improved via a substantial reduction size of labour force, whereas output growth has been rather modest.Although in most of the other countries the restructuring process has been less intense, most of the sectors studied have improved in terms of overall output and labour productivity, especially since the mid-1990s.
URN:NBN:fi:bof-20140807156
Keywords: D24; G21; 330; banks; service production; productivity